SINGLE-LEVEL METHOD OF BEHAVIORAL ONLINE TESTING OF DISTRIBUTED INFORMATION SYSTEMS - Martynyuk, O. N.; Tamim, Ahmesh; Drozd, O. V.; Molotkov, O. N.; Smoktii, K. V. (Systems and Technologies, 2019)
The article considers a single-level method of behavioral online testing with recognition of the reference behavior of DIS. The method features are the evolu-tionary search for reference behavior in the flow of DIS functioning, paralleliza-tion of operations of check recognition and evolutionary development of check populations. The method allows to reduce the complexity and time of check, to make it compatible with the real functioning of the DIS.